2019
DOI: 10.1177/0033294119878399
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Emotion Regulation Training Program on Mental Well-Being

Abstract: This research aimed to validate an Emotion Regulation Training program cultivating resilience, strengthening interpersonal communication, and enhancing emotional intelligence. A community sample of 104 participants were assigned to either an intervention ( n =  51) or nonactive control ( n =  53) group matched by age and gender. In addition, data were gathered via a cognitive performance test conducted pre- and postmeasurement in a subset of the larger sample ( n =  19 intervention, n =  19 control). Results r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 56 publications
0
18
0
9
Order By: Relevance
“…There is evidence that trainings to improve reappraisal are associated with reduced negative interpretations and negative emotions in response to stress ( Tabibnia, 2020 ; Webb et al, 2012 ). Cognitive reappraisal is also associated with a decrease in depression symptoms and worry, and with an increase in mental health wellbeing ( Burklund et al, 2014 ; LeBlanc et al, 2020 ), as well as with reduced unhealthy behaviours such as dietary restriction ( Mazlomi Barm Sabz et al, 2020 ), binge eating ( Haynos et al, 2016 ) and alcohol consumption ( Svaldi et al, 2014 ). This evidence points towards the potential of using emotion regulation trainings aimed at improving reappraisal in order to face psychological stress and protect from using risky behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that trainings to improve reappraisal are associated with reduced negative interpretations and negative emotions in response to stress ( Tabibnia, 2020 ; Webb et al, 2012 ). Cognitive reappraisal is also associated with a decrease in depression symptoms and worry, and with an increase in mental health wellbeing ( Burklund et al, 2014 ; LeBlanc et al, 2020 ), as well as with reduced unhealthy behaviours such as dietary restriction ( Mazlomi Barm Sabz et al, 2020 ), binge eating ( Haynos et al, 2016 ) and alcohol consumption ( Svaldi et al, 2014 ). This evidence points towards the potential of using emotion regulation trainings aimed at improving reappraisal in order to face psychological stress and protect from using risky behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…It established the sense of well-being. As previous findings suggested, factors related to teacher's well-being are the ability to perform coping behavior resulted in lower stress level [3], [15], the skill to remain focus and mindful [4], and becoming resilient [13], [14]. Teacher IK felt that the application of emotion regulation strategies allowed her to learn new skills control emotions and gain more focus in maintaining teacher-student relationship.…”
Section: Teacher's Well Beingmentioning
confidence: 89%
“…How teachers perform emotion regulation strategies has attracted many researchers in educational psychology and then provide remarkable findings that teacher's emotion regulation effect classroom management [10], improve teaching effectiveness [1], [11], maintain teacher's ideal professional image [2], [11], and enhance the sense of well-being [3], [4], [12]. A number of research has shown that practicing emotion regulation skill may result on the improvement of the social and emotional competence [4], stress management [3], [4], [13], resilience [13] [14], and emotional well-being [4], [13], [15]. Martin E. P. Seligman, the founding father of positive psychology, defines well-being as a broad construct comprised by some indicators: positive emotions, engagement, meaning, positive relationship, and accomplishment.…”
Section: Introductionmentioning
confidence: 99%
“…However, no studies have been found in young Spanish couples that promote health and well-being through education of emotional competences in sentimental relationships. Therefore, it is important to evaluate the effectiveness of dyadic interventions in emotional education in couples, based on a strong theoretical framework and with attention to the methodology used [50].…”
Section: Why Do We Need Effective Interventions In Emotional Educatiomentioning
confidence: 99%
“…To sum up, this work aims to awaken the interest of psychologists and researchers in the emotional education of young couples [16]. Effective intervention programs appear to be useful for young people to learn to express, understand and regulate their emotions as a couple, and, as a consequence, establish higher-quality relationships [50]. This may be an appropriate way to enhance the general health and well-being of this population, and, at the same time, prevent social problems such as partner violence [7].…”
Section: Strengths Limitations and Future Considerationsmentioning
confidence: 99%